1999
DOI: 10.1002/(sici)1097-0290(19991120)65:4<416::aid-bit6>3.3.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oxygen enrichment on morphology, growth, and heterologous protein production in chemostat cultures of Aspergillus niger B1‐D

Abstract: The response of steady state chemostat cultures of a recombinant Aspergillus niger (B1-D), secreting both a heterologous enzyme (Hen Egg White Lysozyme [HEWL]) and a native enzyme (Glucoamylase), to varying levels of O2 enrichment of the process gas was evaluated. Formation of both the native and the foreign enzyme increased with increasing O2 supply. Conversely, biomass levels and total extracellular protein levels were generally not increased under O2 enriched conditions. Two distinct micromorphologies were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
1
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 0 publications
3
25
1
2
Order By: Relevance
“…Gassing batch cultures of A. niger with O 2 -enriched air decreases the size of hyphal elements and increases the proportion of active cytoplasm, but hyphal adhesion occurs at the highest level of O 2 enrichment (50% v/v) (Wongwicharn et al 1999). Similar results have been found where O 2 enrichment results in branched and shorter hyphae (Kreiner et al 2003;Bai et al 2004).…”
Section: The Effects Of Oxidative Stress On Fungal Morphologysupporting
confidence: 73%
See 1 more Smart Citation
“…Gassing batch cultures of A. niger with O 2 -enriched air decreases the size of hyphal elements and increases the proportion of active cytoplasm, but hyphal adhesion occurs at the highest level of O 2 enrichment (50% v/v) (Wongwicharn et al 1999). Similar results have been found where O 2 enrichment results in branched and shorter hyphae (Kreiner et al 2003;Bai et al 2004).…”
Section: The Effects Of Oxidative Stress On Fungal Morphologysupporting
confidence: 73%
“…Oxidative stress, caused by over-oxygenation to bioreactors, adversely affects the production of a recombinant protein from A. niger (Wongwicharn et al 1999;Bai et al 2004). Thus, mitigating oxidative damage could ultimately increase protein production by fungi.…”
Section: The Effects Of Oxidative Stress On Enzyme Production In Fungimentioning
confidence: 99%
“…The morphology of Aspergillus, filamentous growth forms and/or the shape and size of pelleted growth forms as well as the branching frequency, is influenced by many factors including specific strain properties [22] but also environmental factors such as spore numbers in the inoculum or type of inoculum [23][24][25], medium composition [23,[26][27][28], dissolved oxygen concentration [29][30][31], pH [23,32], temperature [23,27], reactor type and scale [27,33], and power input [23,25,26,28,29,[33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the intra-and extracellular CAT and GOX production was related neither to the fungal biomass nor to the size of the pellets, and that catalase production may be directly related to the external layer of the pellet and precisely to the morphology of the hyphae in this region. It has been shown that the ramified morphological form of the hyphae has an important influence on the formation of a range of metabolites by filamentous fungi (Wongwicharn et al, 1999) and that secretion of proteins is primarily associated with the apical and subapical regions, therefore called the active regions (Nykanen et al, 1997;Agger et al, 1998). Immobilization in PVA/alginate beads probably changed some characteristics of the culture, are reflected in the protein excretion and enzyme activities.…”
Section: Discussionmentioning
confidence: 99%